Wasatiyyah Values Appreciation in the Syariah Governance as Consumer Understanding Education Mechanisme towards Islamic Banking System - Mohd Izzat Amsyar Mohd Arif; Ruzian Markom; Mohd Arif Ismail (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2017)
The concept and values of wasatiyyah are fundamental in Islamic banking practice as the syariahlaw has delineated basic muamalat principles as an operation guideline for the banking industry.So that, all kind of extreme characteristics may be prevented. The principles of wasatiyyah prohibitany element which overlooks the permitted limit namely gambling, uncertainty (gharar), usury,fraud and so on. These elements have to be avoided in life because they were clearly prohibited byAllah SWT due to their oppressive nature especially towards the unfortunate such as the poor orlow-income group. This prohibition is also attached with the heavy intimidation in the hereafter.The Islamic banking system upholds the concept of wasatiyyah through the values of fairness,trust, transparency and accountability which are instilled through the syariah governance system.The appreciation of these values is proposed to be a part of the new curriculum for the financialawareness subject has been presented by the Malaysia government in the 13th Parliamentarysession. It is important to educate and enhance the understanding of the public especially the youngabout the Islamic banking system as an alternative to avoid the prohibited conventional bankingsystem.